Physiological and biomechanical load parameters in life-saving - Daniel, K.; Klauck, J. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
To determine a profile of load during life-saving heart rate, lactic acid concentration and dynamic forces were measured as parameters of load during the event "50 m saving a dummy". Lactic acid determinations were made during rest and then at four intervals in the recovery phase after a maximum effort. The mean values of lactate accumulation for the total group (testpersons: n = 17 m/f) showed an increased concentration from the first to the second sample for all testpersons and a significant decrease from the second to the fourth measurement (P < 0.05). The curve patterns of all test persons were similar to those of competitive swimmers over sprint distances. Heart rate was recorded and stored during swimming and recovery every 5 seconds. The mean heart rate showed a pattern, which highlighted the influence of the diving reflex (P < 0.01). Dynamic forces were measured using a strain gauge load cell fixed between the traction rope and a gondola driving above the surface of a 50 m indoor pool. During tethered swimming drag forces increased because of added loads for about 10 to 19% depending on the kind of load (v 1.2 m/s const.).